Eksistensi Pendidikan Non Formal Daerah Industri (Studi Fenomena TPQ Al-Amin Bambe Driyorejo) - Nurul Karimah; Ach. Khusnan; Barudin (Jurnal Pendidikan Agama Islam Miazhar, 2023)
The development and existence of the Qur'an Education Park, the Qur'an Education Park is one of the tools to instill Islamic values ​​from an early age to the younger generation. In carrying out these functions, because of its non-formal nature, the implementation of the Al-Qur'an Education Park is in accordance with the socio-cultural and economic conditions of the community. Bambe Village is an industrial area with a majority Muslim community, it is quite strategic to construct a non-formal Islamic Education Institution, because this area is majority of the people are neutralist and nationalist but still maintain religious values. This study aims to describe, (1) The existence of TPQ Al-Amin non-formal education in the industrial area of ​​Bambe Driyorejo Village, (2) The role of TPQ Al-Amin non-formal education in the industrial area of ​​Bambe Driyorejo Village. This research is a descriptive study using a qualitative approach. The subjects of this study included the head of the TPQ, educators, guardians of students, and local community leaders. Data collection techniques used are observation, interviews, and documentation. Data analysis was carried out through several stages, namely: data collection, data reduction, data presentation, and data verification. The validity of the data using triangulation techniques. The results of the study were seen from: (1) The existence of TPQ Al-Amin non-formal education can be seen from the support and cooperation of all levels of society in Bambe Driyorejo Village. (2) TPQ Al-Amin's non-formal education in industrial areas is the answer to people's anxiety about their children's religious education. In addition to learning the skills to read and write the Koran, TPQ Al-Amin also instills basic Islamic religious values ​​in the younger generation, educates children in religious knowledge, and balances children's formal education in schools with religious education, as well as older children. take the time to study the Koran instead of playing.